2015
DOI: 10.1177/0956462415591414
|View full text |Cite
|
Sign up to set email alerts
|

‘The waiting game’: are current chlamydia and gonorrhoea near-patient/point-of-care tests acceptable to service users and will they impact on treatment?

Abstract: The objective of this study was to assess the length of time service users were prepared to wait for chlamydia and gonorrhoea (CT/GC) near-patient/point-of-care test (NP-POCT) results and to determine the possible effect on management. Individuals attending two UK clinics from November 2013 to February 2014 were surveyed asking the maximum length of time they would wait for CT/GC NP-POCT results after consultation. Linked CT/GC prevalence and treatment rates were analysed. A total of 1817 participants were sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The test's rapidity enhances the possibility of implementation as a POCT, enabling test and treat strategies with patients diagnosed and treated in the same clinical visit, and is potentially rapid enough to be incorporated into clinical practice with minimal change to clinical pathways. To date, a major barrier identified for STI POCT implementation has been patient willingness to wait, even for a 90-minute rapid test [11], [18], and the major changes to clinic care pathways necessary to incorporate rapid tests as POCTs as part of SHC consultations [11], [12]. Consequently, CT/NG GeneXpert implementation has enabled a same-day or next-day results service, rather than a POCT test and treat strategy [19], [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…The test's rapidity enhances the possibility of implementation as a POCT, enabling test and treat strategies with patients diagnosed and treated in the same clinical visit, and is potentially rapid enough to be incorporated into clinical practice with minimal change to clinical pathways. To date, a major barrier identified for STI POCT implementation has been patient willingness to wait, even for a 90-minute rapid test [11], [18], and the major changes to clinic care pathways necessary to incorporate rapid tests as POCTs as part of SHC consultations [11], [12]. Consequently, CT/NG GeneXpert implementation has enabled a same-day or next-day results service, rather than a POCT test and treat strategy [19], [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research is required to determine the willingness to wait of patients offered single-step GeneXpert screening, and to test our assumption that patients with an abnormal CXR would be willing to wait for their GeneXpert result. Wiliness to wait is likely, however, to be low as demonstrated by a recent UK study which showed that only 8.5% of individuals tested for chlamydia and gonorrhoea were willing to wait over 90 minutes for a point-of-care test result, despite their having sought testing 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study examined the potential cost benefit of near-patient mPOC testing for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) in a clinic based on reduction of contact attempts [7]. As part of the study, 1,356 patients who had CT/NG nucleic acid amplification tests (NAAT) also completed a questionnaire to ascertain the maximum time patients were willing to wait after consultation for CT/NG test results and thus the potential for immediate treatment of individuals testing positive while preventing unnecessary treatment of patients who tested negative.…”
Section: Turnaround Time and Patient Impactmentioning
confidence: 99%